Legal Recognition and Media Representation of Sign Languages: South African Sign Language and New Zealand Sign Language as case studies - Mashala, Gontse Godfrey (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.